Assessing Open Science Practices in Phytolith Research - Emma Karoune (Open Quaternary, 2022)
Open science is an integral part of all scientific research, but the extent of open science practices in phytolith research is unknown. Phytolith analysis examines silica bodies that are initially formed within and between plant cells during the life of the plant but become deposited in sediments once the plant dies. The use of phytoliths in archaeobotanical and palaeoecological studies has been increasing in recent years resulting in an upsurge in publications. The aims of this article are to assess open science practices in phytolith research by reviewing data and metadata sharing, and open access, in a sample of journal articles containing primary phytolith data from 16 prominent archaeological and palaeoecological journals (341 articles). This study builds on similar studies conducted for zooarchaeology (Kansa 'et al'. 2020) and macro-botanical remains (Lodwick 2019). This study shows that 53% of papers shared data in any format but only 4% of papers contained reusable data, 74% included some pictures of phytolith morphotypes for identification purposes, 69% had a fully described method, 47% used the International code for phytolith nomenclature (ICPN 1.0) and only 13% of articles were open access. Steps forward are then proposed, including planning for open projects, making more articles openly accessible and implementing the FAIR data principles, to use as a starting point for discussions in the wider phytolith and archaeological communities to develop guidelines for greater integration of open science practices.